The Vietnam War with Walter Cronkite. Volume 3 [videorecording (DVD)] - Cronkite, Walter; Bradley, Ed, 1941-2006; Kuralt, Charles, 1934-1997; Rather, Dan; Safer, Morley; Simon, Bob, 1941-2015 (Marathon Music & Video, 2003)
The third segment in a 3-part film history of the Vietnam War, as chronicled by Walter Cronkite and other CBS News correspondents. America pulls back looks at the war during the last days of U.S. involvement. It is a shocking story of poor morale, drug use and innocent victims of a brutal war. The end of the road: As America struggles for a way out, the so-called, "peace with honor," the final chapter of America's involvement in the Vietnam War unfolds. As Saigon falls, witness the last tragic act in a long and divisive war. Legacies: Journeys with veterans and people that lived through the conflict to revisit the places and memories of a distant but unforgotten war.